Modelling the effects of phosphor converted LED lighting to the night sky of the Haleakala Observatory, Hawaii. Issue 2 (17th May 2018) - Aubé, M; Simoneau, A; Wainscoat, R; Nelson, L
ABSTRACT: The goal of this study is to evaluate the current level of light pollution in the night sky at the Haleakala Observatory on the island of Maui in Hawaii. This is accomplished with a numerical model that was tested in the first International Dark Sky Reserve located in Mont-Mégantic National Park in Canada. The model uses ground data on the artificial light sources present in the region of study, geographical data, and remotely sensed data for (1) The nightly upward radiance, (2) The terrain elevation, and 3) The ground spectral reflectance of the region. The results of the model give a measure of the current state of the sky spectral radiance at the Haleakala Observatory. Then, using the current state as a reference point, multiple light conversion plans are elaborated and evaluated using the model. We can thus estimate the expected impact of each conversion plan on the night sky radiance spectrum. A complete conversion to white light emitting diodes (LEDs) with correlated colour temperature of 4000  and 3000 K are contrasted with a conversion using phosphore-convertred amber LEDs. We include recommendations concerning the street lamps to be used in sensitive areas like the cities of Kahului and Kihei, and suggest best lighting practices related to the colour of lamps used at night.